Gene Expression of CD70 and CD27 Is Increased in Alopecia Areata Lesions and Associated with Disease Severity and Activity - Radwa El- Sayed Mahmoud Marie; Noha M. Abd El-Fadeel; Yara El-Sayed Marei; Lina M. Atef (Dermatology Research and Practice)
Background. Alopecia areata (AA) is an acquired hair loss disorder induced by a cell-mediated autoimmune attack against anagen hair follicles. CD27-CD70 is a receptor-ligand complex which enhances T helper and cytotoxic T cell activation, survival, and proliferation. The overstimulation of this complex can lead to a lack of tolerance and the development of autoimmunity. Objectives. This study aimed to assess the gene expression of CD27 and CD70 in patients with AA. Methods. CD70 and CD27 mRNA expressions were evaluated by a quantitative real-time polymerase chain reaction in scalp biopsies from 40 AA patients (both AA lesions and non-lesional areas) and 40 healthy controls (HCs). The Severity of Alopecia Tool (SALT) score was used to assess AA severity. Patients were evaluated for signs of AA activity, including a positive hair pull test and dermoscopic features of black dots, broken hairs, and tapering hairs. Results. The gene expression of CD70 and CD27 was significantly higher in AA lesions than in non-lesional areas (p<0.001 for both) and HCs (p=0.004,p=0.014, respectively). There were significant positive correlations between AA severity and gene expression of CD70 (p<0.001) and CD27 (p=0.030) in AA lesions. Significant associations were detected between signs of AA activity and lesional gene expression of CD70 and CD27. Additionally, CD70 and CD27 gene expression was significantly lower in non-lesional biopsies compared to HCs (p<0.001). Conclusion. Gene expression of CD70 and CD27 was increased in AA lesions and was associated with disease severity and activity. Thus, both molecules can be a predictor of AA severity and activity. Furthermore, the expression was reduced in non-lesional scalp areas. Thus, a lack of CD27 and CD70 expression may initially predispose to immunological dysregulation and the development of AA.